DIVULGANDO NOVA CHAMADA DE ARTIGOS PARA NÚMERO TEMÁTICO VOLTADO PARA "DIÁLOGOS NO CAMPO DA ANTROPOLOGIA DA ALIMENTAÇÃO" - Fabiana Bom Kraemer; Shirley Donizete Prado (Universidade do Estado do Rio de Janeiro, 2014)
We begin this editorial by wishing everyone a good reading and by thanking readers and authors for their support onthe advancement and dissemination of our publishing. The increasingly upcoming volume of original papers remains consistent.Thus, we were able to publish 15 high-standard original articles in this issue, along with five abstracts of theses and dissertations defended in the Graduate Programs in Food, Nutrition and Health from the Nutrition Institute of UERJ (State University of Rio de Janeiro). These papers addressed objects that identify the field of Food and Nutrition in Brazil, namely: food, nutriment and / or nutrient. The original articles scaffold issues arising from several areas of knowledge that make up the scientific field of Food and Nutrition. For instance, one of the studies refers to the social identity of obese individuals;another study regards Policies on Food and Nutrition; two epidemiological studies address Nutrition; two studies on food production, another study onfood chemical composition and microbiological quality; and, for last, eight studies that concern Clinical Nutrition. Maintaining the growth trajectory of Demetra is key to our editorial policy. In a previous opportunity, we successfully invested in the dissemination of research articulating knowledge and practices on Food and Humanities. By following this thread, we would like to announce our next investment: the creation of a special issue that will focus on the discussion on food knowledge and practice that have as core theme dialoguesinFood Anthropology. In this new thematic issue, to be published in 2015, we aim to create opportunities for the dissemination of research and reflections that address studies on the significant social and cultural arrangements of various human groupings, depicted from the analysis of their eating habits. We are extremely excited and encouraged with great expectationsto announceand acknowledge our partnership with researchers Martín César Tempass, from theUniversidade Federal de Pelotas, and Mônica Chaves Abdala, from theUniversidade Federal de Uberlândia, in coordinating this promising thematic issue. We hope that this new thematic issue will contribute to a greater dialogue between the Human and Social Sciences and the Health Sciences in Food and Nutrition research. Thus, we invite nutritionists, anthropologists, sociologists, historians, psychologists, and other professionals, to discuss such matter that requires multidisciplinary perspectives. We hope, once again, that researchers will reliably submit their work for publication and continue to collaborate andstrengthen our publishing, which is committed to providingfree and public access opportunity toscientific knowledge. DOI: http://dx.doi.org/10.12957/demetra.2014.14064